Sitagliptin can inhibit the development of hepatic steatosis in high-fructose diet-fed ob/ob mice - Sujishi, Tetsuya (J Clin Biochem Nutr, 2015)
The beneficial effect of dipeptidyl peptidase-4 inhibition on diet-induced extra-pancreatic effects, especially on liver tissue remains poorly understood. Thus, we made the experimental designs as follows; five-week-old male ob/ob mice, which develop type 2 diabetic mellitus and nonalcoholic fatty liver disease by taking a high-carbohydrate diet (HCD), were divided into a group in which a HCD was given for 8 weeks as control, and another in which a HCD added with 0.0018% sitagliptin was given for 8 weeks. Hepatic steatosis was seen in all mice, but the mean grade of steatosis in the sitagliptin-administrated mice was significantly decreased. The acetyl-CoA concentrations were lower in sitagliptin-administrated mice, although the differences were not significant. However, the malonyl-CoA concentrations were significantly lower in sitagliptin-administrated mice. The expression of acetyl-CoA carboxylase 1 was inhibited in sitagliptin-administrated mice, irrespective of expressions of carbohydrate responsive element-binding protein (ChREBP) or sterol regulatory element-binding protein (SREBP)-1c. In conclusion, sitagliptin may affect the development of nonalcoholic fatty liver disease by inhibiting the production of malonyl-CoA and thus synthesis of fatty acids in the liver.